ANALISIS KECERDASAN SOSIAL SISWA DALAM PEMBELAJARAN IPA - Sudarto Sudarto; Asriadi Asriadi; Andi Muhammad Yudha (JOEL: Journal of Educational and Language Research, 2023)
This research is a qualitative research that aims to describe the social intelligence of the VB grade students at SD Negeri 2 Manurunge, Tanete Riattang District, Bone Regency. The research subjects were VB Grades homeroom teachers and 25 persons of VB Grade. Collecting data using interviews, observation and questionnaires. Data analysis techniques namely data reduction, data display, and drawing conclusions. The results and conclusions of the study were the social intelligence of VB Grade students at SD Negeri 2 Manurunge, Tanete Riattang District, Bone Regency, namely: being able to be a good listener, generally having a sense of empathy, and being able to position themselves as a student at school, students have focus and dare to appear in front of his friends to convey his ideas or ideas with confidence when carrying out the science learning process